Pre-release studies on Zophodia Tapiacola (Dyar) (Pyralidae : Lepidoptera) : a biological control agent against jointed cactus, Optuntia Aurantiaca Lindley - Hoffmann, John Hugh (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1976)
Jointed Cactus, Opuntia aurantiaca Lindley (see frontispiece), is the most important weed plant in South Africa, infesting approximately, 1,2 X 10¹° M² and costing approximately R240 000 per annum. Tordon herbicide effectively kills jointed cactus bushes to which it is applied. However, apart from being expensive and damaging to beneficial vegetation, spray programmes have not successfully controlled the weed because most small O. aurantiaca plants are impossible to detect in the field. Biological control may provide a solution to the problem. Two insects, the cochineal bug, Dactylopius austrinus De Lotto and the pyralid moth, Cactoblastis cactorum Berg., already exercise a degree of control over the weed. The introduction into South Africa of other natural enemies such as Zophodia tapiacola (Dyar) from Argentina, South America, may reduce the density of jointed cactus to below an acceptable economic threshold. Any insect considered for release should not colonise and destroy beneficial plants of which the culivated spineless cacti are the most vulnerable. Pre-release studies on Z. tapiacola have shown that it can only colonise a few species of low growing cacti and that it will not damage the large spineless cacti or other desirable plants. Further, the moths are relatively fecund and each larva destroys significant amounts of O. aurantiaca during its development. Consequently, Z. tapiacola is not only considered safe for release but it has the potential to act as a successful biological control agent of O. aurantiaca in South Africa.
Keywords: Pyralidae; Lepidoptera; Cactus; Weeds -- Biological control; Opuntia